Teachers' personal experiences of sexual initiation motivating their sexuality education messages in secondary schools in Kampala, Uganda. Issue 2 (4th March 2022) - de Haas, Billie; Hutter, Inge
ABSTRACT: Little is known about how teachers' personal sexual experiences influence their motivations and practices when teaching sexuality education. Cultural schema theory was used to explore teachers' personal experience of the onset of sexual activity and explain how sexuality education teaching is influenced by such experiences. In-depth interviews were conducted with 40 secondary school teachers in Kampala, Uganda. The interviews were transcribed verbatim and analysed using principles of grounded theory. Findings show that while teachers' personal experience of sexual initiation did not directly align with the content of their messages, due to the centrality and evocative function of these schemas these experiences strengthened teachers' motivation to teach sexuality education because they enabled them to empathise with students. The study concludes that teachers' personal experiences of sexual initiation provide intrinsic motivation for teaching sexuality education. The inclusion of dialogues and activities which encourage self-reflexivity in teacher education and training may improve the delivery of sex, sexuality and relationships education.